Vestibular dysfunction in pediatric patients with cochlear implantation: A systematic review and meta-analysis - Wu, Qiong; Zhang, Qin; Xiao, Qianwen; Zhang, Yuzhong; Chen, Zichen; Liu, Shuyun; Wang, Xueyan; Xu, Yong; Xu, Xin-Da; Lv, Jingrong; Jin, Yulian; Yang, Jun; et al. (Frontiers in Neurology, 2022)
Objective Vestibular dysfunction may delay the achievement of balance and perception milestones in pediatric patients after cochlear implantation (CIM). Methods A strategic literature search was done following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched the PubMed, Medline, Embase, Web of Science, and Cochrane Library databases from inception to July 2022. Studies were included on the otoliths, semicircular canals, and balance function changes in children after CIM. Two reviewers independently assessed the level of evidence, methodological limitations, risk of bias, and characteristics of the cases. Matched pre- and postoperative vestibular functional test data, including ocular and cervical vestibular-evoked myogenic potential (oVEMP and cVEMP), caloric test, video head impulse test (vHIT), and Bruininks-Oseretsky Test 2 (BOT-2), were used to calculate the relative risk of vestibular disorders. Subgroup analyses were performed according to surgical approach, CIM device status, and etiology. Results Twenty studies that met the inclusion criteria were selected for the meta-analysis. We observed significant vestibular dysfunction in pediatric patients with CIM. The results showed a statistically significant increase in abnormal cVEMP response (RR = 2.20, 95% CI = 1.87, 2.58, P < 0.0001), abnormal oVEMP response (RR = 2.10, 95% CI = 1.50, 2.94, P < 0.0001), and abnormal caloric test results (RR = 1.62, 95% CI = 1.20, 2.19, P = 0.0018) after implantation. Statistically significant differences were not found in the vHIT test results of all three semicircular canals before and after the operation (P > 0.05). Regarding static and dynamic balance, we found significantly poorer BOT-2 scores in children with CIM than in the normal group (mean difference = −7.26, 95% CI = −10.82, −3.70, P < 0.0001). Conclusion The results showed that vestibular dysfunction might occur after CIM in pediatric patients. Some children experience difficulties with postural control and balance. Our results suggest that a comprehensive evaluation of vestibular function should be performed before and after CIM.